2013
DOI: 10.16925/sp.v9i19.709
|View full text |Cite
|
Sign up to set email alerts
|

Posible superfetación en una coneja raza NZB (Oryctolagus cuniculus) concomitante a retraso del desarrollo intrauterino (RDIU)

Abstract: Reportes de casoPosible superfetación en una coneja raza nzb (Oryctolagus cuniculus) concomitante a retraso del desarrollo intrauterino (rdiu) resumen. Los trastornos reproductivos del conejo son complejos y numerosos incluyendo rarezas como la superfetación (sf). Se describe un posible caso de sf descubierto accidentalmente, asociado a distocia en una coneja de la raza nzb, que sufre de severa hemorragia vaginal, postración, hipotermia y no reactiva al estímulo. Durante la palpación, numerosos fetos fueron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most recent possible case of superfetation in rabbits was reported in an obese doe accidentally remated some days after a confirmed pregnancy, in Mexico [21]. Since the fetuses were not responding to the manipulation for extraction, a cesarean was performed.…”
Section: Superfetationmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent possible case of superfetation in rabbits was reported in an obese doe accidentally remated some days after a confirmed pregnancy, in Mexico [21]. Since the fetuses were not responding to the manipulation for extraction, a cesarean was performed.…”
Section: Superfetationmentioning
confidence: 99%
“…What caught the attention was the fact that, among the fetuses, six were overdeveloped, which may have contributed to the problems during labor, and one was severely underdeveloped and covered by a thick green fluid, called meconium, which delimits the intestines of the fetuses and is usually released only at the time of birth. Based on the morphological differences and mating records, the authors postulated that the underdeveloped fetus may have resulted from a superfetation, despite the unclearness regarding how a second implantation occurred [21]. Other studies have been reported previously: one described the case of a pregnant doe that mated a week before giving birth and a second healthy litter was born 23 days after the first [62], and another one described a case in which a doe gave birth twice within two weeks ( [63] as cited by [61]).…”
Section: Superfetationmentioning
confidence: 99%
See 1 more Smart Citation